Optimalisasi Pemetaan Bisnis Menggunakan Triple Layer Business Model Canvas - Adib, Mokh; Suryana, Suryana; Wijaya, Fanji (Image : Jurnal Riset Manajemen, 2023)
Vocational High School as a center of excellence is a solution to increase the business productivity of the school. This study aims to find out the business strategies that have been carried out by schools using the Triple Layer Business Model Canvas (TLBMC) as a tool to explore business model innovations that are oriented towards. Descriptive research method using an approach based on the philosophy of post positivism, purposive, and snowball sampling from the principal, 5 teacher representatives and 5 student representatives at SMK PK Al Ikhlas Susuru Panawangan which is used as a reference source in finding information to start a business strategy. From the results of the study, it was concluded that based on the TLBMC mapping, the economic strata were well described, the use of unfriendly packaging had an impact on not describing the final element of life, and the extent to which the business carried out did not cause negative social impacts. The PMIA score shows a positive value, meaning that the business is appropriate and feasible to continue.